Clinicopathological features and prognosis of familial papillary thyroid carcinoma – a large‐scale, matched, case–control study. (11th August 2015) - Cao, Jun; Chen, Can; Chen, Chao; Wang, Qing‐Liang; Ge, Ming‐Hua
Summary: Objective: It remains controversial whether or not the aggressiveness of familial nonmedullary thyroid cancer (FNMTC) differs from sporadic carcinoma. The aim of this study was to determine the clinicopathological features and prognosis of FNMTC. Design: A matched‐case comparative study. Methods: Three hundred and seventy‐two patients with familial papillary thyroid carcinoma (FPTC) were enrolled as the study group, and another 372 patients with sporadic PTC were enrolled as controls and matched for gender, age, tumour/node/metastasis (TNM) staging and approximate duration of follow‐up. We compared the differences in the clinicopathological features and prognosis between the subgroups. Results: Compared with sporadic PTC, patients with FPTC were more likely to present tumour multicentricity, bilateral growth and a concomitant nodular goitre ( P < 0·05). In papillary thyroid microcarcinoma (PTMC), a higher recurrence rate was noted in patients with a family history of PTC, and this remained independently predictive on multivariate analysis. The patients with FPTC in the second generation showed an earlier age of onset, more frequent Hashimoto's thyroiditis and a higher recurrence rate than the first generation, while the first‐generation offspring of patients had a higher incidence of nodular goitre than the second generation. Conclusions: The presence of familial history in PTC indicates an increase in biological aggressiveness, and patients in the second generation may exhibit the 'genetic anticipation' phenomenon. At present, the available data are not sufficient to support a more aggressive approach for FPTC. However, a family history of PTC is an independent risk factor for recurrence in patients with PTMC.